Elements for assistance to patients with hematological malignancies to propose care lines: a scoping review - Mayane Cleisla dos Santos Rocha; Valéria Dantas de Azevedo; Maria de Fátima Lucena dos Santos; Rodolfo Daniel de Almeida Soares; Viviane Euzébia Pereira Santos; Isabelle Campos de Azevedo (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to identify the elements for assistance to patients with hematological malignancies to propose a care line. Methods: this is a scoping review, anchored in the JBI theoretical framework, with searches carried out in April 2021, in eight electronic databases and 10 repositories of theses and dissertations. Results: the final sample consisted of 93 studies, and the main forms of assistance provided that can support a care line for this public were imaging tests, immunophenotyping, chemotherapy regimens, radiotherapy, infection management, assessment of nutritional status, maintenance of oral function, symptom management and screening for second malignancies. Conclusions: the elaboration of a care line for onco-hematologic patients is necessary, considering the complexity surrounding the diagnosis and treatment of hematologic malignancies, in addition to the difficulties that are imposed in relation to access and continuity of care in the network.